Musical performance: A guide to understanding - Rink, John (Cambridge Cambridge University Press, 2002)
This book unravels the complexities of playing music and reveals aspects of learning, playing and responding to music relevant to performances of all levels. A survey of performance through the ages leads to a presentation of basic historical, analytical and psychological concepts. Four chapters follow on teaching, development, practice and memorization. The next section considers the "translation" from score to sound, physical projection, ensemble playing and performance anxiety. The final section addresses the act of listening, the legacy of recordings, music criticism and "performers on performance".